Kinetics and thermodynamics of transpeptidation catalysed by Bacillus subtilis gamma glutamyl transferase - Balakrishna, Sharath; Prabhune, Asmita A. (Indian Journal of Biochemistry and Biophysics, 2017)
Gamma glutamyl transferases (GGT) catalyse the removal (deglutamylation) of the terminal gamma-glutamate residue from compounds such as glutathione and poly-gamma-glutamic acid and its transfer either to a water molecule (hydrolysis) or to a peptide/amino acid (transpeptidation). We analysed the kinetics of Bacillus subtilis GGT (BsGGT) catalysed transpeptidation using gamma-glutamyl-(3-carboxyl)-4-nitroaniline as the gamma-glutamate-donor and glycylglycine (Gly-Gly) as the gamma-glutamate acceptor. Addition of Gly-Gly improved the affinity (Km) of the enzyme for gamma-glutamyl-(3-carboxyl)-4-nitroaniline by nearly 25 times with negligible impact on the rate of deglutamylation (V-max). The asymmetric changes in the kinetic parameters improved the specificity constant (K-cat/K-m.) by about 43 times. BsGGT catalysed transpeptidation was pronounced in conditions that are unfavorable for hydrolysis. Maximum transpeptidation occurred near neutral pH and when the concentration of the gamma-glutamate-donor substrate is lower. The effect of Gly-Gly on the kinetics of BsGGT is contrastingly different from that observed for eukaryotic GGTs. In the case of mammalian GGTs, the addition of Gly-Gly increases both Km and k(cat); and, the specificity constant (K-cat/K-m) remains unaltered